All-incoherent wavelength conversion in highly nonlinear fiber using four wave mixing - Kharraz, Osayd M.; Ahmad, Harith; Forsyth, David I.; Dernaika, Mohamad; Zulkifli, Mohd Zamani; Ismail, Mohd Faizal B.; Mohammad, Abu Bakar B. (SPIE, 2014)
This work describes efficient and polarization insensitive, all-incoherent four-wave mixing wavelength conversion achieved within a short length of highly nonlinear fiber medium, created by using both spectrally sliced pump and probe channels from a single-amplified spontaneous emission source coupled to two narrowband Fiber Bragg grating (FBG) filters. This simple and cost-effective scheme is capable of generating a downconverted probe channel across a 17.2-nm wavelength span, while still maintaining a high conversion efficiency of around −22 dB and an optical-signal-to-noise ratio of ∼21 dB. The effects of pump power, FBG detuning, and polarization are also reported. © 2014 Society of Photo-Optical Instrumentation Engineers (SPIE) [DOI: 10.1117/1.OE.53.9.096112]